Enhanced design of fiber grating fabry-perot laser for dense wavelength division multiplexing systems - Al-Musawi, Hisham K. Hisham (2012)
Semiconductor laser diodes (SLDs) have been widely used in wavelength-divisionmultiplexing (WDM) systems due to small size, low power consumption, fast response,and its ability to perform direct modulation at moderate bit rates. A major obstacle preventing closer channel spacing is the drift of emission wavelength with ambient temperature variation. Therefore, with the development of dense WDM (DWDM) systems, lasers with narrow linewidth, high side mode suppressed ratio (SMSR), low chirp, low cost, and stable dynamic single-mode operation are indispensable. In recent years, fiber grating Fabry-Perot (FGFP) laser is proposed as an alternative light source for WDM systems, which can generate light with highly stable wavelengths. This is because; the emission wavelength of such laser depends only on the Bragg wavelength of fiber grating (FG), thus, independent of chip temperature and injection current. However, FGFP laser output experiences phase fluctuations due to the quantum nature of the light. In addition, ambient temperature variation causes fluctuation in the gain spectrum, threshold current, and other cavity parameters. Furthermore, external optical feedback (OFB) level (i.e. the light reflected back from grating fiber) significantly affects the performance of FGFP laser, which may fluctuate the FGFP light intensity and varies the dynamical and spectral behaviors of the laser. These will produce unwanted effect such as mode hopping and/or the coherence collapse. In this thesis, the performance of the FGFP laser is enhanced by optimizing parameters in its original model. The effect of ambient temperature variation, OFB, injection current, cavity volume, nonlinear gain compression factor, spontaneous emission factor, linewidth enhancement factor, antireflection (AR) coating reflectivity, external cavity length, amplitude coupling coefficient, and fiber Bragg grating (FBG) parameters on the performance characteristics of the FGFP laser, namely dynamic response (transient response, turn-on time delay, relaxation oscillation frequency), modulation responses (intensity modulation, frequency modulation) and noise characteristics (relative intensity noise, phase noise, linewidth characteristics) has been demonstrated. In this study, we modeled FGFP laser based on the three-mirror laser cavity model. The reflection from the external mirror is combined with the reflection of the laser end front facet, ending up with a complex-valued effective reflection coefficient, which is equivalent to two-mirror cavity. The expressions that describe the laser characteristics have been modified by considering the effect of temperature, external OFB and other external cavity parameters. This thesis is presented based on the alternative format which has been approved by University Putra Malaysia’s Senate, which is the manuscript-based format. The major difference between this alternative format and the conventional ones is that, this format uses published papers in place of the regular chapters on the results and discussion. The first paper, which deals with the turn-on time delay characteristics of the semiconductor diode lasers, is a comment paper, contains new results of the effect of the carrier recombination rate coefficients on the laser turn-on time delay which is published in Optics and Laser Technology. This journal in indexed by ISI Thomson Scientific with 2010 impact factor of 1.616. The results in this paper corrected the misconception to the behavior of the carrier recombination rate coefficients on the laser turn-on time delay, which has been published by Zhang et al, Opt. & Laser Technol. 39 (2007) 997– 1001. This paper is based on a numerical closed-form equation for turn-on time delay in terms of all carrier recombination rate coefficients. The comparison between our results and those that has been published was based on the practical and physical concepts for the operation principle of semiconductor lasers. It has been shown that the main effect of increasing any of the carrier recombination rate coefficients is to increase the turn-on time delay (not to decrease, as in original report), which is due to increase of the carrierrecombination rate. This fact has been supported further by investigating the effect of carrier recombination rate coefficients on the laser threshold current. The second paper contains a comprehensive analysis on FGFP laser peak intensity modulation and relaxation oscillation frequency (ROF) characteristics, which is published in Optical Review, the Japan Society of Applied Physics. This journal in indexed by ISI Thomson Scientific with 2010 impact factor of 0.55. The frequency of the relaxation oscillation plays an important role in determining laser response. The study is performed by modifying the general expression of ROF equation, which is often expressed in terms of the carrier and photon lifetimes. It is demonstrated that by optimizing design parameters, ROF increased significantly to produce high flat frequency operation. The third paper investigated the FGFP laser modulation response characteristics, which is published in Optics and Laser Technology. This journal in indexed by ISI Thomson Scientific with 2010 impact factor of 1.616. In this paper, a unified and comprehensive study on the small-signal intensity modulation (IM) and frequency modulation (FM) characteristics of FGFP laser have been numerically conducted. This study has been presented by developing the general expressions of the intensity and frequency modulations response using the single-mode laser rate equation. It was shown that with laser dimension optimization, IM and FM responses with low peak amplitude, high flat frequency operation and high temperature stability can be obtained. The most important feature of a semiconductor laser used in optical communication systems is the ability to operate with low relative intensity noise. In the fourth paper, we present a comprehensive analysis on the FGFP laser relative intensity noise (RIN) characteristics, which is published in IEEE Journal Quantum Electronics. This journal is indexed by ISI Thomson Scientific with 2010 impact factor of 2.48. In this paper, the analysis has been performed numerically by developing a set of nonlinear single-mode laser rate equations. It is shown that by laser optimization, the relative intensity noise level of FGFP laser can be reduced significantly. Finally, the phase noise characteristics of a semiconductor laser are of interest in evaluating the performance of a coherent optical communication system. Because of the quantum nature of the lasing process, the laser output exhibits phase as well as intensity fluctuations. The fifth paper discussed the phase noise characteristics of FGFP laser,which is published in the Journal of Modern Optics. This journal in indexed by ISI Thomson Scientific with 2010 impact factor of 0.988. In this paper, the analysis was performed numerically by modifying the general expression of the laser phase noise equation. Through a comprehensive analysis, the results clearly show that by laser optimization, the FGFP laser phase noise performances significantly improved.